From "coup-teaching" to co-teaching: engaging with faculty in the one-shot classroom - Foster, Ali (My University, 2017)
How do we handle “coup-teaching” moments, when the conflicting expectations of faculty and the IL instructor can derail a one-shot IL session? This lightning talk will explore how the co-teaching model allows information literacy instructors to rethink faculty engagement in the one-shot classroom.
Presented in May 24, 2017 at WILU, held at the University of Alberta in Edmonton, Alberta.
Keywords: information literacy; one-shot instruction; collaboration